Implementasi Maqasid syariah Pada Pemiayaan BSI Pensiun Sebagai Solusi Keuangan Syariah Berkelanjutan - Fio Aditya; Hayatul Millah; Ahmad Fajri (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to analyze the implementation of Maqasid Sharia in the BSI Pensiun financing product and evaluate its role as a sustainable, inclusive, and holistic Islamic financial solution for retirees in Indonesia. Using a descriptive qualitative approach, the research explores the extent to which the principles of Maqasid Sharia – namely the preservation of religion, life, intellect, lineage, and wealth – are reflected in the pension financing scheme. The findings indicate that BSI Pensiun serves not only as an economic financing tool but also as a means of safeguarding Islamic values in daily life. This study recommends enhancing public awareness regarding the benefits of Maqasid-based Islamic financing and fostering product innovation to expand its reach and impact in the future. These findings contribute to the development of more responsive, relevant, and Sharia-aligned Islamic financial products.